Sistem Informasi Manajemen Data Asrama Mahasiswa Kabupaten Waropen Di Manokwari Berbasis Web Menggunakan MERN Stack: Web-Based Management Information System for Student Dormitory Data of Waropen Regency in Manokwari Using MERN Stack - Musa Faisal Duwiri; Josua Josen A. Limbong (JISTECH: Journal of Information Science and Technology, 2025)
Student dormitories play an important role in supporting smooth studies, especially for students who come from remote areas. Waropen Regency provides student dormitories in Manokwari Regency, but their management still faces various obstacles, such as manual recording, lack of administrative transparency, and difficulties in monitoring facilities. This research aims to develop a web-based dormitory information system that can improve the efficiency and accuracy of managing data on active, inactive, and alumni students, as well as facilitate the verification process for Study Plan Cards (KRS), which was previously done manually. The system also includes features for student complaints regarding dormitory facilities, scholarship data collection, inventory data, and report printing in PDF format. The development was carried out using modern technology based on React.js on the interface side, Express.js and Node.js on the server side, and MySQL  as a  relational  database.  The development results show that this system is capable of providing a responsive interface, supporting transparent administrative processes, and facilitating communication between students and administrators. Thus, this information system is considered effective in addressing the needs of student dormitory management in Waropen Regency in the digital era.